Model Penguatan Kapasitas Perempuan dan Keluarga Berbasis Masyarakat: Strategi Partisipatif dalam Pencegahan Stunting dan Pengasuhan Anak di Desa Sukaraja Kabupaten Kuningan - Bambang Rustanto; Irniyati Samosir; Sri Ratna Ningrum; Tuti Kartika; Ayi Haryani; Aryohaji Istyawan (Jurnal Pengabdian Tri Bhakti, 2026)
Stunting and the low quality of child parenting remain major challenges in family development in rural areas, particularly due to limited access to information, low health literacy, and the persistence of traditional parenting practices. This condition was also identified in Sukaraja Village, Kuningan Regency, where many families still had limited understanding regarding stunting prevention and responsive child parenting. This community service program aimed to develop a community-based model for strengthening women’s and family capacities through a participatory approach to support stunting prevention and child parenting improvement. The program was implemented in RW 01 of Sukaraja Village in August 2025 using the Participatory Technology Development (PTD) approach. The implementation methods included coordination with village authorities and posyandu cadres, participatory assessment through Focus Group Discussion (FGD), community-based intervention planning, educational and training activities, and monitoring through cadre assistance. The results showed an increase in participants’ understanding of the importance of the First 1,000 Days of Life, responsive parenting practices, nutritional fulfillment, sanitation, and stunting prevention. Participants also began applying positive communication patterns in child parenting and utilizing local food resources as affordable nutritional alternatives for families. This program demonstrates that a community-based participatory approach can strengthen the capacities of women and families in creating a healthy, responsive, and sustainable parenting environment as part of local efforts to accelerate stunting reduction.